We Forgot the Middle Class! Inequality Underestimation in a Changing Sub-Saharan Africa - Clementi, F.; Dabalen, A.L.; Molini, V.; Schettino, F. (Springer Nature, 2020)
The creation of national middle classes and the changes in consumption patterns in many Sub-Saharan African (SSA) countries suggest reconsidering the way welfare and consequently inequality is typically measured. Using only consumption to measure welfare can lead to an important loss of information regarding the real welfare of the top 10–20% of the welfare distribution that is generally referred as “middle class” in these countries. This paper proposes a method capable of correcting the middle-class part of the consumption distribution using information coming from the income distribution of the same surveys. Results from 6 SSA countries indicate an increase of about 20% in the Gini index.